Development of Simple Pyphox-based Regular Straight Motion Practicum Tools - Jeli; Chandra, Artha Nesa (Impulse: Journal of Research and Innovation in Physics Education, 2024)
This research aims to develop a practicum tool for Regular Straight Motion (RSM) based on the Phyphox application as an innovation in physics learning that is more interactive and accurate. The research method uses an experimental approach, where the Phyphox application is utilized to record time and distance data automatically, replacing manual methods that often face accuracy problems due to human error. The research successfully demonstrated that the use of the Phyphox application can increase measurement accuracy to 95% and reduce the human error rate by 30%. It also enables real-time data visualization, which not only facilitates the analysis of relationships between variables but also helps students better understand physics concepts. In addition, the app enriches students' learning experience by increasing their motivation and engagement, and supports the mastery of 21st century skills such as data analysis and use of technology. The development of Phyphox-based tools is expected to be a strategic step to modernize physics learning, prepare students to face global challenges, and make a real contribution in improving the quality of physics education in the digital era. This shows that technology has great potential in transforming education, especially in improving the effectiveness and efficiency of the teaching and learning process.